2015
DOI: 10.1039/c5lc00346f
|View full text |Cite
|
Sign up to set email alerts
|

The microenvironment of double emulsions in rectangular microchannels

Abstract: The flow environment in inner cores of water-in-oil-in-water (w/o/w) microfluidic double emulsions has a significant impact on industrial applications of such systems. For example, in the case of shear sensitive cells compartmentalised in the cores, high shear conditions may be deleterious. This study reports on the flow characteristics of w/o/w inner cores in comparison to those in single water -in-oil (w/o) microdroplets of equal size moving in the same microchannel, resolved by means of micro -particle imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…In balancing both [PI] and [R*] convective transport is neglected because [PI] is exposed and converted into radicals evenly across the droplet and [R*] is consumed much faster than it is transported. While it has been clearly established that recirculating three-dimensional flows do form in microdroplets as they flow through a microchannel 61,62 , it was assumed that these interior flows diminish with polymerization, and our experimental results validate this assumption. The oxygen specie balance equation (Equation 3) addresses two events: oxygen-radical scavenging and the diffusive oxygen flux into the droplet.…”
Section: Resultssupporting
confidence: 60%
“…In balancing both [PI] and [R*] convective transport is neglected because [PI] is exposed and converted into radicals evenly across the droplet and [R*] is consumed much faster than it is transported. While it has been clearly established that recirculating three-dimensional flows do form in microdroplets as they flow through a microchannel 61,62 , it was assumed that these interior flows diminish with polymerization, and our experimental results validate this assumption. The oxygen specie balance equation (Equation 3) addresses two events: oxygen-radical scavenging and the diffusive oxygen flux into the droplet.…”
Section: Resultssupporting
confidence: 60%
“…The velocity gradients were calculated from the measured velocities with the least squares method. Based on the velocity gradients, the shear rates were estimated as ϵ Ma et al, 2015). The shear stress t was calculated as t = hϵ, where h was the fluid viscosity and set to 1.05 ± 0.01 mPa·s (Helfield et al, 2016a).…”
Section: Shear Stress Calculationmentioning
confidence: 99%
“…Shear stresses are critical in cell printing, and therefore we performed hydrodynamic simulations in Comsol Multiphysics to explore the microenvironment in GelMa plugs of various viscosities moving at set velocities within the tubing. The simulations show that the strain rates are lower in plugs than in continuous single‐phase flow, and that the reduction in the strain rates is more significant in higher viscosity plugs. After the droplet‐to‐oil viscosity ratio exceeds 50, the droplet interior circulation is mostly suppressed and the strain rates approach zero (Figures S10 and S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 94%
“…A key consideration in performing cell printing is to reduce the shear stress . Hydrodynamic simulations showed that the shear strains in GelMa plugs are reduced by comparison with single‐phase flow, suggesting that the encapsulated cells are protected (Figures S10 and S11, Supporting Information). Indeed, patterned GelMa microrods containing living cells, including both immortalized and primary cells, showed ≈90% viability and typical cellular behaviors, including migration and proliferation in culture after printing, demonstrating that the shear stress in the tubing, the exposure to oil, the process of phase‐transfer and photo‐crosslinking are compatible with 3D cell culture.…”
Section: Discussionmentioning
confidence: 99%